Scientific Literacies for Change Making: Equipping the Young to Tackle Current Societal Challenges - Tasquier, Giulia; Knain, Erik; Jornet, Alfredo (Frontiers in Education, 2022)
The recent global emergence of youth movements concerning climate change, such as the school strikes movement originated by climate activist Greta Thunberg, demonstrates young people’s engagement with societal challenges that involve science in complex ways and have an impact on their present and future. Dealing with the threatening challenges and profound changes that characterise our era requires the development of knowledge and skills to navigate the uncertainty and complexity of science as part of society and everyday life. How can we support school students in transforming the base of knowledge and experiences to face the ongoing crises and contribute as individuals, citizens and active participants in democratic society to enable the transformation that is called for? We address this broader question through a study framed within the Horizon 2020 project Science Education for Action and Engagement towards Sustainability (SEAS), aimed at promoting new forms of scientific literacy and skills to empower students to become agents of change. Most centrally, SEAS aims at incorporating a transformative dimension that is often lacking in going conceptions of scientific literacy. In SEAS, school and school science are conceived as involving learning and transformation across three spheres— the practical, the political, and the personal—where both individuals and their institutional contexts change as participants gain agency over their learning processes. In this paper, we illustrate this approach and present the analysis of a first pilot iteration within the project’s Italian Local Network, which show the kind of individual/collective dynamic that the project’s transformative activities afford.